2014
DOI: 10.1136/jclinpath-2014-202255
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologists’ approach to keratoacanthoma: a multisite survey of regional variation in Great Britain and Ireland

Abstract: An extreme variation in approach is highlighted by this survey. We believe a multidisciplinary team approach to the diagnosis of KA is essential. There seems to be a need for a carefully considered clinicopathological study, backed up by molecular studies, to better understand the natural biology of this diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 3 publications
0
20
0
2
Order By: Relevance
“…38 Numerous studies have analysed the possible mechanisms underlying the oncogenesis of KA and SCC or focusing on how to differentiate these lesions using histologic criteria, immunohistochemical markers, and chromosomal abnormalities. 4,[39][40][41][42][43][44][45][46] Many have considered immunohistochemistry to be of limited value in the routine diagnosis of these tumors, and additional studies are needed. Notably, epidermal growth factor receptor (EGFR) anomalies appear to be more common in SCC than in KA, yet immunohistochemical expression of EGFR has been identified in both lesions.…”
Section: Discussionmentioning
confidence: 99%
“…38 Numerous studies have analysed the possible mechanisms underlying the oncogenesis of KA and SCC or focusing on how to differentiate these lesions using histologic criteria, immunohistochemical markers, and chromosomal abnormalities. 4,[39][40][41][42][43][44][45][46] Many have considered immunohistochemistry to be of limited value in the routine diagnosis of these tumors, and additional studies are needed. Notably, epidermal growth factor receptor (EGFR) anomalies appear to be more common in SCC than in KA, yet immunohistochemical expression of EGFR has been identified in both lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety of 218 respondents (41%) indicated that their local histopathologists distinguish KA from SCC; 27 (12%) indicated that they do not; and the remainder (101, 46%) noted variation. In a U.K. histopathology department survey, the ratio of coded SCC to KA varied from 2·5 : 1 to 139 : 1 confirming widespread reporting variations . In a clinical trial, centralized expert histopathologist review could overcome this issue.…”
Section: Management Choices For Keratoacanthoma‐like Lesions On the Ementioning
confidence: 99%
“…In a U.K. histopathology department survey, the ratio of coded SCC to KA varied from 2Á5 : 1 to 139 : 1 confirming widespread reporting variations. 8 In a clinical trial, centralized expert histopathologist review could overcome this issue. Of note, in two phase II vemurafenib trials, central review of SCC histology specimens led to reclassification as KA in up to 94Á4% of cases.…”
mentioning
confidence: 99%
“…The role of immune system in the appearance and regression of tumors is controversial, but nevertheless, must be taken into consideration. [11][12][13][14] Although the predisposing genes for the appearance of solitary sporadic KA are not exactly known, studies have shown that KA is a monogenic condition rather than being digenic 15,16 .…”
Section: Etiology and Geneticsmentioning
confidence: 99%
“…Another study identified p53 gene mutations in approximately 40 percent of KAs, indicating that the mutation is closely related to the nuclear accumulation of the p53 protein. 12,14,15,16 Rare sporadic pruritic generalized eruptions of KA are known as Gryzbowski's generalized eruptive keratoacanthoma (GEKA). The solitary and multiple mucosal KAs that are rarely observed in the course of GEKA point to a different origin of these tumors, and the possibility of differentiation from the upper segment hair follicle like cells.…”
Section: Etiology and Geneticsmentioning
confidence: 99%